Dynamics of an age-of-infection cholera model - Fred Brauer; Zhisheng Shuai; P. van den Driessche (Mathematical Biosciences and Engineering)
A new model for the dynamics of cholera is formulated that incorporates both the infection age of infectious individuals and biological age of pathogen in the environment. The basic reproduction number is defined and proved to be a sharp threshold determining whether or not cholera dies out. Final size relations for cholera outbreaks are derived for simplified models when input and death are neglected.